Deciphering taxonomic and functional diversity of fungi as potential bioindicators within confluence stretch of Ganges and Yamuna Rivers, impacted by anthropogenic activities. (August 2020) - Samson, Rachel; Rajput, Vinay; Shah, Manan; Yadav, Rakeshkumar; Sarode, Priyanka; Dastager, Syed G.; Dharne, Mahesh S.; Khairnar, Krishna
Abstract: River confluences are interesting ecological niche with limited information in respect of the structure and the functions of diverse microbial communities. Fungi are gaining global attention as promising biological spectacles for defining the trophic status of riverine systems. We condense existing knowledge in confluence diversity in two Indian rivers (i.e. Ganges and Yamuna), by combining sediment metagenomics using long read aided MinION nanopore sequencing. A total of 63 OTU's were observed, of which top 20 OTU's were considered based on relative abundance of each OTU at a particular location. Fungal genera such as Aspergillus, Penicillium, Kluveromyces, Lodderomyces, and Nakaseomyces were deciphered as potential bio indicators of river pollution and eutrophication in the confluent zone. In silico functional gene analysis uncovered hits for neurodegenerative diseases and xenobiotic degradation potential, supporting bioindication of river pollution in wake of anthropogenic intervention. Graphical abstract: Image 1 Highlights: First preliminary investigation on the mycobiome across the confluence of River Ganges and Yamuna. Presence of fungal genera, is being reported as bioindicator of river pollution. The fungal diversity of River Ganges does not appear to vary in the wake of confluence. Functional diversity of fungi from Ganges was influenced by the convergence of River Yamuna.